STABILITAS PERFORMA DAN REALIBILITAS IPAL DOMESTIK DENGAN KOMBINASI AERASI SECARA INTERMITTENT DENGAN RESIRKULASI EFLUEN DAN MICROBUBBLE GENERATOR - Johan Syafri Mahathir Ahmad; Hafasatya Maharani Putri; Nurul Ainun Santoni; Sri Puji Saraswati (FROPIL (Forum Profesional Teknik Sipil), 2021)
Recently, various technology has been applied to the domestic wastewater treatment plant (WWTP); however, the reliability, compliance to standard and performance are not well understood. This study discusses the reliability of WWTP in Bulaksumur Residence in terms of compliance to effluent quality standards (for direct discharge) and class VI water quality standards (for irrigation water potential use). The WWTP operates continuously, and its performance was observed for 82 days. This WWTP uses an intermittent aeration system by utilizing wastewater recirculation coupled with a microbubble generator nozzle. From the observations, the WWTP shows good and stable performance indicated by its TSS, COD, PO4-P removal efficiency of 68,9±12,9%, 78,4±9,8%, 45,3±8,6% and 63,4±13,7%, respectively, as well as its nitritation, nitration and denitrification efficiency (83,1±7,9%, 97,6±2,0% and 67,2±19,3%, respectively). Effluent quality of TSS (4,6±3,4 mg/l), COD (13,9±6,6 mg/l), and NH3-N (2,4±2,4 mg/l) shows 100% compliance to both regulation standards for effluent discharge and class IV water quality. Likewise for NO3-N (2,8±0,5 mg/l) also show 100% compliance to both standards. As for NH3-N (2,4±2,4 mg/l ) and NO2-N (0,22±0,99) only showed similar poor reliability of 8.3% compliance to class IV water quality standard.